Ubezpieczenia społeczne duchownych w prawie kanonicznym - Domaszk , Arkadiusz (Seminare. Poszukiwania naukowe, 2022)
The present paper raises the issue of social insurance for the clergy in the Catholic Church. The first part provides the historical background, norms of the 1917 Code of Canon Law and indications of the Second Vatican Council. The next part discusses the current decrees of canon law and solutions adopted in Poland. At present, the Church has abandoned the beneficial system. Systemic church solutions are based on state legislation. In their absence, decisions are made by the Bishops’ Conference, as well as individual particular Churches. It refers both to social and health insurance.